STRATEGI PEMBINAAN MORAL MELALUI LAYANAN KONSELING TERHADAP SANTRI PUTRI PONDOK PESANTREN AL FALAH SUMBER GAYAM - Ezzah, Nailatul; Sofiyatus Zahriyah; Haisyisyiatus Shalehah, Azmi; Jamilah, Raudhatul (Ash-Shudur : Jurnal Bimbingan dan Konseling Islam, 2025)
This study aims to examine the strategy of moral development through counseling services for female students at the Al Falah Islamic Boarding School in Sumber Gayam. The scope of the study includes the strategic approach taken by the Islamic boarding school in shaping the moral character of female students through individual and group counseling services. The subjects of this study were female students residing and participating in activities at the Al Falah Islamic Boarding School, as well as the counselors or mentors directly involved in these moral development services.This study used a qualitative approach with a case study method. Data collection was conducted through observation and in-depth interviews. Data were analyzed descriptively and qualitatively, with the stages of data reduction, data presentation, and conclusion drawing. The results indicate that the strategy of moral development through counseling services at the Al Falah Islamic Boarding School encompasses three main approaches: (1) a preventive approach through Islamic values education, (2) a curative approach with individual counseling for students facing moral or behavioral problems, and (3) a rehabilitative approach in the form of continued guidance involving mentoring and moral habituation programs. Counseling services have proven effective in developing moral awareness and a sense of responsibility among students toward themselves, their environment, and religious values. This study recommends strengthening the capacity of counselors and integrating counseling programs into the student character development curriculum to achieve more optimal and sustainable results.